Valdosta Project Change, Scrapbook, April 1999 - Valdosta Project Change (Lowndes County Historical Society, 1999)
4/1- Four NYPD officers indicted on murder charges: Killing immigrant could get officers 25 years to life: Associated Press; 4/4- Demonstrators protest against police brutality- Associated Press; 4/7- Blacks make progress, but racism still exists- Scripps Howard News Services; 4/14- ‘Do we really want to talk about race?’: Race issues forum aims to begin community dialogue- no author; 4/21- Forum tonight aimed at beginning local dialogue on race- no author; 4/22- Dealing with our demons: Local residents come together for exchange on race relations- Brian Lawson; 4/24- Coca-Cola Co. sued for race discrimination: Plaintiffs claim soft drink firm has ‘glass ceiling’- Associated Press ; 4/25- More efforts needed to combat racism- no author; 4/26- Houseal says role models are desperately needed- Joe Dunlop; 4/27- Ethnicity not high on kids’ agendas- Weenam Chua; 4/28- Habitat proposal would eliminate substandard housing- Jodi M. Scott;
Valdosta Project Change. “Valdosta Project Change Scrapbook, April 1999,” Lowndes County Historical Society. Valdosta State University Archives and Special Collections, MS-181: Valdosta Project Change Scrapbook Collection, 1997-2003. 1 PDF document and scans, 14 pages. 410 MB (430,598,859 bytes).
Keywords: Clippings (Books, newspapers, etc.); Discrimination--Prevention; Lowndes County Historical Society (Valdosta, Ga.); Nonprofit organizations; Project Change; Race discrimination--Prevention; Racism; Scrapbooks; Valdosta (Ga.) -- Social conditions; Valdosta (Ga.); Valdosta Daily Times; Valdosta Project Change